THE EFFECTIVENESS OF MAKE A MATCH MODEL ASSISTED BY GRAPHIC MEDIA TO INCREASE STUDENTS’ LEARNING ACTIVITIES IN SCIENCE LEARNING AT GRADE V - Salsabila Aprillia; Erfan Ramadhani; Arief Kuswidyanarko (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The problem in this study was that students were in a passive state in learning activities, causing a lack of learning activities. This was because the teacher did not apply learning models or learning media when providing materials. The population in this study were grade five students of SD Negeri 15 Sungailiat. In this study, class VB students were grouped as the experimental class who were taught by using Make A Matching model with the aid of graphic media, and class VA students were grouped as the control class who were taught by using a conventional model. The total number of samples in this study were 31 students in each class. The method used in this study was a quantitative method with a quasi-experimental design type of nonequivalent control group design. Data collection techniques were carried out through observation, questionnaires, and documents. The data analysis technique used the ttest (independent sample t-test) with the help of SPPS Version 23. The results of this study indicated that Ha was accepted or there was a significant difference in students’ learning activities in the control class and the experimental class. This was seen from the results of sig. (2-tailed) 0.000 < 0.05, with an average score difference of 34.36%. Thus, this study concluded that Make A Matching model assisted by graphic media were more effective to increase students’ learning